MR spectroscopy using static higher order shimming with dynamic linear terms (HOS‐DLT) for improved water suppression, interleaved MRS‐fMRI, and navigator‐based motion correction at 7T. Issue 3 (14th February 2020) - Boer, Vincent O.; Andersen, Mads; Lind, Anna; Lee, Nam Gyun; Marsman, Anouk; Petersen, Esben T.
Abstract : Purpose: To interleave global and local higher order shimming for single voxel MRS. Single voxel MR spectroscopy requires optimization of the B0 field homogeneity in the region of the voxel to obtain a narrow linewidth and provide high data quality. However, the optimization of local higher order fields on a localized MRS voxel typically leads to large field offsets outside that volume. This compromises interleaved MR sequence elements that benefit from global field homogeneity such as water suppression, interleaved MRS‐fMRI, and MR motion correction. Methods: A shimming algorithm was developed to optimize the MRS voxel homogeneity and the whole brain homogeneity for interleaved sequence elements, using static higher order shims and dynamic linear terms (HOS‐DLT). Shimming performance was evaluated using 6 brain regions and 10 subjects. Furthermore, the benefits of HOS‐DLT was demonstrated for water suppression, MRS‐fMRI, and motion corrected MRS using fat‐navigators. Results: The HOS‐DLT algorithm was shown to improve the whole brain homogeneity compared to an MRS voxel‐based shim, without compromising the MRS voxel homogeneity. Improved water suppression over the brain, reduced image distortions in MRS‐fMRI, and improved quality of motion navigators were demonstrated using the HOS‐DLT method. Conclusion: HOS‐DLT shimming allowed for both local and global field homogeneity, providing excellent MR spectroscopy data quality, as well as good field homogeneity for interleaved sequence elements, even without the need for dynamic higher order shimming capabilities.